RISK BASED APPROACH DAN TREN MENDATANG DALAM INTERNAL AUDIT TOOLS & TECHNIQUES - DYAH AYU LARASATI; YUSTRIDA BERNAWATI (Jurnal Bisnis dan Akuntansi, 2020)
Internal auditors have begun to shift from a traditional approach to risk-based approach. This article will review the previous literature on risk based audit approach, risk based audit plan and the forthcoming trends for internal audit tools and techniques (TTs) based on Common Body of Knowledge (CBOK) survey in 2007 and 2010. Based on surveys conducted by IIA in 2007 and 2010 the risk based audit plan continues to occupy the top position in the TTS used by internal auditors. It is argued that the risk-based audit plan will continue to be used by auditors in the future, because internal auditors conceive that if the internal audit plan is based on key risks that exist within the organization, it will enhance Chief Audit Executive (CAE)'s ability to match the audit plan to organizational needs..